2009
DOI: 10.1128/aem.02108-08
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Recognition Force Microscopy Shows that Outer Membrane Cytochromes OmcA and MtrC Are Expressed on the Exterior Surface of Shewanella oneidensis MR-1

Abstract: Antibody recognition force microscopy showed that OmcA and MtrC are expressed on the exterior surface of living Shewanella oneidensis MR-1 cells when Fe(III), including solid-phase hematite (Fe2O3), was the terminal electron acceptor. OmcA was localized to the interface between the cell and mineral. MtrC displayed a more uniform distribution across the cell surface. Both cytochromes were associated with an extracellular polymeric substance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 28 publications
4
98
0
Order By: Relevance
“…oneidensis expresses the two outer membrane cytochromes MtrC and outer membrane cytochrome A (OmcA) under ferric iron-reducing conditions. In vitro evidence suggested that OmcA and MtrC build a high-affinity complex, but this in vitro finding is not supported by in vivo colocalization studies (47,85). The role of these outer membrane cytochromes in respiration does not seem to be interchangeable (85).…”
Section: Extracellular Electron Acceptorsmentioning
confidence: 74%
“…oneidensis expresses the two outer membrane cytochromes MtrC and outer membrane cytochrome A (OmcA) under ferric iron-reducing conditions. In vitro evidence suggested that OmcA and MtrC build a high-affinity complex, but this in vitro finding is not supported by in vivo colocalization studies (47,85). The role of these outer membrane cytochromes in respiration does not seem to be interchangeable (85).…”
Section: Extracellular Electron Acceptorsmentioning
confidence: 74%
“…Previous studies on S. oneidensis used proteinase K susceptibility to demonstrate the cell-surface exposure of MtrC and OmcA (22). Analyses with immunogold localization and functionalized atomic force microscopy also showed the surface localization of MtrC and OmcA (15,23). Here, hybridization with gold-labeled MtrC antibodies demonstrated that MtrC also is exposed on the surface of the MtrCAB proteoliposomes (Fig.…”
Section: Topology Of Mtrcab In Proteoliposomesmentioning
confidence: 81%
“…The evidence that the conductive filaments were involved in extracellular electron transfer in Shewanella was the finding that deletion of the genes for the c-type cytochromes OmcA and MtrC, which are necessary for extracellular electron transfer, resulted in nonconductive filaments, suggesting that the cytochromes were associated with the filaments (7). However, subsequent studies specifically designed to localize these cytochromes revealed that, although the cytochromes were extracellular, they were attached to the cells or in the exopolymeric matrix and not aligned along the pili (24,25,30,40,43). Subsequent reviews of electron transfer to Fe(III) in Shewanella oneidensis (44,45) appear to have dropped the nanowire concept and focused on the first and second mechanisms.…”
mentioning
confidence: 99%